Hubungan Tingkat Pengetahuan Prenatal Yoga dengan Minat Ibu Hamil dalam Mengikuti Kelas Prenatal Yoga di Puskesmas Putri Ayu Kota Jambi - Nurbaiti Nurbaiti; Suci Rahmani Nurita (Jurnal Akademika Baiturrahim Jambi, 2020)
Pregnancy is a natural event experienced by a mother. During pregnancy, the mother will experience physical and mental changes. Changes that occur even provide discomfort for the mother such as back pain, aches in the legs, anxiety, and so forth. Pregnant women are in need of a healthy and fit body, and a relaxed mind, where this condition can be obtained by seeking a regular diet, adequate rest and exercise. To maintain the health of pregnant women pregnancy care needs to be done. One of the treatments for pregnancy is to practice yoga exercises.This study aims to determine the relationship of prenatal yoga knowledge level with the interest of pregnant women in taking prenatal yoga classes. This study uses a cross sectional research design that aims to determine the relationship of the level of prenatal yoga knowledge with the interest of pregnant women in taking prenatal yoga classes at the Puskesmas Putri Ayu in Jambi City. The study population was pregnant women who came to the Puskesmas Putri Ayu Kota Jambi. The sample in this study was taken using accidental sampling techniques as many as 32 people. This research was conducted from January-August 2019 at the Putri Ayu Public Health Center in Jambi City.The results showed that more than half of respondents had good knowledge about yoga (56.3%) and more than half of respondents had a high interest in taking prenatal yoga classes (59.4%) .There was a significant relationship between the level of prenatal yoga knowledge with interest mothers in taking prenatal yoga classes (p = 0.006).It is expected that the Putri Ayu Public Health Center can improve health programs, especially programs for increasing the knowledge of pregnant women about the benefits of prenatal yoga in pregnancy.